Vector-controlled Y-connected three-phase induction motor drives: small-signal stability study during IGBT short-circuit fault - Maryam Naghavi; Mahmood Ghanbari; Reza Ebrahimi; Mohammad Jannati; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The stability analysis is one of the most important elements to describe the performance of AC drive systems under both dynamic and steady-state operating circumstances. This is particularly essential because electric motors operate over a wide range of speeds and utilize complex control systems such as field-oriented control (FOC). This study establishes a small-signal stability analysis (SSSA) in a 1-horsepower vector-controlled Y-connected three-phase induction motor (YCTPIM) drive during an insulated gate bipolar transistor short-circuits failure (IGBT-SCF). In the beginning, a vector control system that is based on the indirect rotor FOC (IRFOC) method is described for post-fault functioning of the YCTPIM while the IGBT-SCF is taking place. After that, a small-signal model of the system that has been provided is explored. This model is based on a voltage-current model, and it is constructed by linearizing the non-linear dynamic equations of the system. During IGBT-SCF, an IRFOC strategy as well as SSSA operations are carried out on the 1-HP, 380 V, and YCTPIM. In this research, both analytical and simulation-based methodologies are applied.